Mechanism of Synthesis of Vaccinia Virus Double-Stranded Ribonucleic Acid In Vivo and In Vitro - Colby, Clarence (1971)
The synthesis of vaccinia virus double-stranded ribonucleic acid (RNA) in infected HeLa cells was sensitive to actinomycin D, suggesting that a deoxyribonucleic acid dependent reaction is involved. Some double-stranded RNA was made in the presence of cytosine arabinoside in infected cells. Double-stranded and complementary RNA were synthesized in vitro by using vaccinia cores. These two observations indicate that some of the double-stranded RNA is read from “early” genes. The double-stranded RNA synthesized in vitro had the same properties as that made in vivo. At least 70% of the double-stranded RNA made in vivo was in ribonuclease-resistant form prior to sodium dodecyl sulfate-phenol extraction. In addition, there was a complementary RNA in infected cells which could be converted to double-stranded RNA by annealing.